A Snapshot on the Cis Chromatin Response to DNA Double-Strand Breaks. Issue 5 (May 2019) - Clouaire, Thomas; Legube, Gaëlle
Abstract : In eukaryotes, detection and repair of DNA double-strand breaks (DSBs) operate within chromatin, an incredibly complex structure that tightly packages and regulates DNA metabolism. Chromatin participates in the repair of these lesions at multiple steps, from detection to genomic sequence recovery and chromatin is itself extensively modified during the repair process. In recent years, new methodologies and dedicated techniques have expanded the experimental toolbox, opening up a new era granting the high-resolution analysis of chromatin modifications at annotated DSBs in a genome-wide manner. A complex picture is starting to emerge whereby chromatin is altered at various scales around DSBs, in a manner that relates to the repair pathway used, hence defining a 'repair histone code'. Here, we review the recent advances regarding our knowledge of the chromatin landscape induced in cis around DSBs, with an emphasis on histone post-translational modifications and histone variants. Highlights: The development of specialized tools has recently provided unprecedented insights regarding the role of chromatin structure in the response to DNA double-strand breaks. High-resolution studies revealed that chromatin is modified on several different scales following DSB induction, ranging from a few kilobases to several megabases. Chromatin modifications at the megabase level may alter the physical properties of the chromatin fiber and regulate long-range chromosomal mobility upon damage. The nature and extent of local chromatin modifications are different upon repair by NHEJ or HR. Repair pathway-specific modifications have the potential to regulate the access of repair factors and the physical properties of the nucleosome, thereby participating in downstream repair events.